2012
DOI: 10.1002/jrs.4034
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of neurotensin‐family peptides on SERS‐active Ag substrates

Abstract: Kinetensin (KN) and its amino acids 1–8 fragment ([des‐Leu9]KN), neuromedin N (NMN), and xenopsin (XP) and its two analogs (XP‐1 and XP‐2) belong to the neurotensin family of peptides and are known to stimulate the growth of human tumors. In this work, we report Fourier transform‐Raman and surface‐enhanced Raman scattering (SERS) studies of these peptides and discuss their structures, orientation, and mode of adsorption onto a highly specific, electrochemically roughened SERS‐active Ag electrode that is charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 61 publications
1
9
0
Order By: Relevance
“…The geometry of these molecules etched on the silver surface was deduced from the observed changes in the Raman bands for the bound versus free species . In a second paper, Podstawka‐Proniewicz and co‐workers studied adsorption of neurotensin‐family peptides on SERS‐active Ag substrates and found that the investigated peptides bound preferentially to the surface by substantial electronic overlap between the metal surface and the pi‐orbitals of the benzene rings of the Phe, Tyr, and Trp residues, which forced them to take close to parallel orientations with respect to the surface . Sassi and co‐workers carried out studies of reversible and irreversible denaturation processes in globular proteins using a variety of spectroscopic probes.…”
Section: Biosciencesmentioning
confidence: 99%
“…The geometry of these molecules etched on the silver surface was deduced from the observed changes in the Raman bands for the bound versus free species . In a second paper, Podstawka‐Proniewicz and co‐workers studied adsorption of neurotensin‐family peptides on SERS‐active Ag substrates and found that the investigated peptides bound preferentially to the surface by substantial electronic overlap between the metal surface and the pi‐orbitals of the benzene rings of the Phe, Tyr, and Trp residues, which forced them to take close to parallel orientations with respect to the surface . Sassi and co‐workers carried out studies of reversible and irreversible denaturation processes in globular proteins using a variety of spectroscopic probes.…”
Section: Biosciencesmentioning
confidence: 99%
“…This proposed assignment agrees with the comprehensive systematic SERS study on the human NT structure in an aqueous solution of nanometer‐sized colloidal silver particles under various environmental conditions, including excitation wavelengths (488.0, 514.5, and 785.0 nm), peptide concentrations (10 ‐4 – 10 ‐6 M), pH levels of the solutions (from pH = 2 to pH = 11), H 2 O/D 2 O solvent exchange conditions, single‐ and multi‐site synthetic structural mutations, and length of the NT fragments . Discussed here normal mode assignments also corresponds with the band assignments for human NT, its mutated fragments and analogues, and related peptides in the solid state and immobilized onto the electrochemically roughened silver substrate …”
Section: Resultsmentioning
confidence: 77%
“…Based on the intensity of the above Tyr and –COO ‐ bands, we propose that together with Phe, the Tyr and –COO ‐ moieties of KN were in close contact with the silver substrate but those of [des‐Leu 9 ]KN were slightly farther from the surface. This finding supports the earlier conclusion about the importance of the Leu 13 COO ‐ residue in the interaction with the silver substrate . The influence of the Leu 13 COO ‐ residue on receptor binding have been also demonstrated in the NT biological activity studies…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the absorption infrared method gives complementary information to the Raman method, supports the Raman analysis, and helps to solve ambiguities during this analysis, the absorption infrared spectra are also examined. Both these methods are commonly employed in both experimental investigations [17][18][19][20] and theoretical calculations [21][22][23] to analyze and compare structures for a large number of conformers of the investigated compounds. Interpreting the Raman and absorption infrared spectra involves explaining spectral regions and wavenumbers based on likely vibrational modes.…”
Section: Introductionmentioning
confidence: 99%